Neutrophyl Lymphocyte Ratio in Tuberculosis Patients and Multi Drug Resistant Tuberculosis Patients - Delores Elisabeth Sormin; Parluhutan Siagian; Bintang YM Sinaga; Putri Chairani Eyanoer (Jurnal Respirologi Indonesia, 2018)
Background: Delayed in diagnosis and treatment of tuberculosis will increase the risk of MDR TB. WHO recommends Xpert MTB/RIF as diagnostic tools to identify MDR TB. Availability of Xpert MTB/RIF is still limited, another diagnostic tool is needed. Neutrophyl lymphocyte ratio (NLR) was presumed to be able to identify the probability of MDR TB. The aim of this study is to evaluate the comparison of NLR in tuberculosis and MDR TB patients. Methods: This is an analytic descriptive study with case series approach in Adam Malik General Hospital Medan. This study held since January – December 2015 with number of sample as much as 100 bacteriological confirmed TB patients and 100 MDR TB patients. We performed leukocyte differential count from peripheral blood examination to obtain NLR Result: Mean NLR of TB patient 4.62±2.37 and MDR TB 3.28±1.44. There was significant difference of NLR between both groups using Mann-Whitney test (P=0.001). The cut off value by ROC analysis was 2.91 with sensitivity, specificity, positive predictive value, negative predictive value and accuracy was 77%, 50%, 60.6%, 68.4% and 63.5% respectively. Conclusion: There was significant difference of NLR between bacteriological confirmed TB patients and MDR TB patients. Value of NLR